2020
DOI: 10.31925/farmacia.2020.5.2
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Liver Disease in Diabetic Patients as Risk Factor for Poor Prognosis of Covid-19: An Update of Potential Mechanisms and Treatment Considerations

Abstract: In the global context of COVID-19 outbreak, scientific efforts have been directed to investigate the risk factors associated with the development of severe illness. Emerging evidence linked the metabolic syndrome to more severe forms of the disease. The majority of the patients with these risk factors develop hepatic injury, particularly those previously diagnosed with nonalcoholic fatty liver disease (NAFLD). NAFLD is the most common cause of chronic liver disease, affecting a quarter of the population worldw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…There are no specific treatments for COVID-19 infection yet, although many candidate therapies are being evaluated in clinical trials [ [5] , [6] , [7] , [8] ] and several COVID-19 vaccines are approved or under evaluation for approval by authorities [ [9] , [10] , [11] ]. Initially, social distancing, along with increasing population testing, are the only effective measures to control the pandemic but with several consequences on long-term [ [12] , [13] , [14] ]. Public health measures include non-pharmacological interventions that can be used to reduce and delay community transmission [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are no specific treatments for COVID-19 infection yet, although many candidate therapies are being evaluated in clinical trials [ [5] , [6] , [7] , [8] ] and several COVID-19 vaccines are approved or under evaluation for approval by authorities [ [9] , [10] , [11] ]. Initially, social distancing, along with increasing population testing, are the only effective measures to control the pandemic but with several consequences on long-term [ [12] , [13] , [14] ]. Public health measures include non-pharmacological interventions that can be used to reduce and delay community transmission [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SARS-CoV-2 is genetically related to SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV) that are known to impair liver function through direct (translocation of the virus from gut to liver) or indirect mechanism (inflammation, ischemia, others) [ 35 ]. Co-morbid conditions such as obesity and dysmetabolism are shown to be associated with severe COVID-19 by exacerbating the infection, which eventually leads to the cytokine storm [ 36 ]. Studies have also found NAFLD in COVID-19 patients to be associated with elevated alanine aminotransferase (ALT) and aminotransferase (AST), which may lead to unfavorable clinical outcomes in this population [ 22 , 26 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding COVID-19 severity, 36.3% (n = 50) patients were classified as non-severe and 63.7% (88) patients as severe. The median in-hospital stay was 16 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) LFT showed that 73.9% (n = 102) patients had at least one abnormal parameter upon hospital admission, and lactate dehydrogenase (LDH) was the most frequent (81.5%, n = 106). The injury pattern was mostly hepatocellular (64.6%, n = 84), while cholestatic liver enzymes were increased in the later stages of the disease.…”
Section: Baseline Characteristics Of Enrolled Patientsmentioning
confidence: 99%
“…In a recently published systematic review carried out by our team, we described the inter-relationship between MAFLD, T2DM and COVID-19. Patients with MAFLD presented severe forms of SARS-CoV-2 infection, had longer viral shredding time and a higher probability for developing abnormal liver function tests (LFT) from admission to discharge [ 11 ]. Numerous interconnected metabolic and inflammatory pathophysiologic consequences link T2DM and MAFLD to COVID-19 severity; MAFLD causes insulin resistance with dysfunctional fatty acid metabolism, generating a state of low-grade inflammation that seems to impair immune responses that contribute to a greater chance of COVID-19 “cytokine storm” [ 12 ].…”
Section: Introductionmentioning
confidence: 99%